Optimalisasi Penerapan Literasi Informasi di Perpustakaan SMA Negeri 1Padang - Septiani, Meuthia; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
The purpose of writing this paper are: (1) to describe the implementation of information literacy at the library of SMA Negeri 1 Padang, (2) to describe the barriers found in implementing the information literacy at library SMA Negeri 1 Padang. Collecting data was done interview and direct information to trough the librarian of SMA Negeri 1 Padang based on data analyzing, it can be concluded: First, the student of SMA Negeri 1 Padang had made use the information technology very well, meanwhile the librarian of SMA Negeri 1 Padang was not capable to help the student to find the information properly by not implementing information literacy program, information literacy model, information retrieval, and user education the library of SMA Negeri 1 Padang, so that the optimalization of information did not run well. Second, the cause of the implementing information literacy at the libarary SMA N 1 Padang was that the librarian had not know the information literacy, so that the implementation of information literacy was hard to apply optimally.